tristatefabricatorsinc

07-09-2006, 09:28 PM

Hello...

I think I am doing this one correctly, but I wanted to make sure I am solving in the correct steps...

z^3-5(z^3-1)+3[z+4(z^2-11)]

I got...

z^3 - 5^3 + 6 + 3[z + 4z^2 -44]

= -4z^3 + 9 + z + 4z -44

= -4z^3 + 5z -35 for final answer

I think I am doing this one correctly, but I wanted to make sure I am solving in the correct steps...

z^3-5(z^3-1)+3[z+4(z^2-11)]

I got...

z^3 - 5^3 + 6 + 3[z + 4z^2 -44]

= -4z^3 + 9 + z + 4z -44

= -4z^3 + 5z -35 for final answer